Ophthalmic manifestations of acute leukaemias - Němčanská, Sabina; Stěpanov, Alexandr; Němčanský, Jan (Czech and Slovak Ophthalmology, 2018)
Background and aims: To determine the incidence of ocular pathological findings in a group of patients with acute leukemia. To define the predictive value of the presence of the ocular pathological findings. Materials and methods: Retrospective evaluation of a group of 67 patients with acute leukemia (age 1–75 years) examined at the Ophthalmology Clinic, Faculty Hospital Ostrava, from 2005 to 2014. Results: Ocular pathological findings were found in 13 patients of the group (19.4 %) - 7 patients with acute myeloid leukemia (10.9 %) and 6 patients with acute lymphoblastic leukemia (8.5 %). 10 patients died due to of the underlying disease. Ocular pathological findings were found in 6 of them (60 %). A higher prognostic value was found in a group of patients with AML. Conclusion: Ophthalmology examination is a necessary part of the examination of patients with acute leukemia. This prognostic benefit is particularly significant in patients with AML.
Keywords: oční symptomy; oftalmoskopie; lidé; Middle Aged; Adult; Prognosis; leukemie; prognóza; Fundus Oculi; akutní myeloidní leukemie; Female; statistika jako téma; dítě; retrospektivní studie; retina; Eye Manifestations; diagnostické techniky oftalmologické; Retina; Humans; Diagnostic Techniques, Ophthalmological; fundus oculi; Ophthalmoscopy; akutní lymfatická leukemie; lidé středního věku; Rothovy skvrny; Statistics as Topic; mužské pohlaví; Precursor Cell Lymphoblastic Leukemia-Lymphoma; ženské pohlaví; Leukemia; Male; fundus leacaemicus; Aged; Retrospective Studies; Child; dospělí; Leukemia, Myeloid, Acute; senioři